Morphology and Chemical Analysis of the Metathoracic Scent Glands System in Adelphocoris suturalis (Hemiptera: Miridae) - Zhang, Zhilin (Oxford University Press, 2014)

(untitled) (J Insect Sci)
The morphological structure of the metathoracic scent glands (MTGs) in Adelphocoris suturalis was observed by utilizing scanning electron microscope (SEM). Also, the secretions of MTGs in male and female were analyzed by using gas chromatography–mass spectrometry (GC-MS). The result showed that the MTGs comprised a reservoir and paired lateral glands, which are connected to a reservoir by duct. The MTGs belong to the diastomian type. A usually depressed channel extends from opening downward the middle of metathorax, a tongue-like structure was covered by bristles and mushroom-shaped cuticular structures, known as evaporative area. In GC-MS investigation, differences were found in quantitative or qualitative compositions of the substances between the two sexes. In our study, hexyl butyrate was the most abundant compound in the MTGs of A. suturalis , comprising ∼85% of total secretions in both female and male, respectively. 4-oxo-(E)-2-hexenal (5.22%) was the second most abundant compound in female MTGs secretions, whereas octacosane (2.42%) followed hexyl butyrate in male MTGs secretions.